2022
DOI: 10.1186/s43042-022-00356-z
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual developmental disorder with dysmorphic facies and ptosis caused by copy number variation including the BRPF1 gene in Peruvian patient

Abstract: Background Intellectual developmental disorder with dysmorphic facies and ptosis (MIM #617333) is a very rare condition, characterized by more than 80% by language delay, intellectual disability, gross motor development delay, broad nasal bridge, hypertelorism, and hypotonia. This condition exhibits as autosomal dominant inheritance and is caused by a heterozygous variant in the BRPF1 gene. Additionally, the copy number variation in the terminal region of chromosome 3p (MIM #613792) has been sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Additionally, some patients exhibit skeletal deformities (72%, 31/43), including hand (brachydactyly and brachymetacarpia) and foot (clubfoot or syndactyly) differences. However, a minority of patients with IDDDFP experience seizures (21%, 9/43) and structural brain abnormalities (50%, 10/20), often characterized by abnormal white matter signals under MRI and corpus callosum thinning [3,[5][6][7][8][9][10][11][12][13]. The affected family members in our report exhibited typical facial dysmorphisms of IDDDFP.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Additionally, some patients exhibit skeletal deformities (72%, 31/43), including hand (brachydactyly and brachymetacarpia) and foot (clubfoot or syndactyly) differences. However, a minority of patients with IDDDFP experience seizures (21%, 9/43) and structural brain abnormalities (50%, 10/20), often characterized by abnormal white matter signals under MRI and corpus callosum thinning [3,[5][6][7][8][9][10][11][12][13]. The affected family members in our report exhibited typical facial dysmorphisms of IDDDFP.…”
Section: Discussionmentioning
confidence: 65%
“…Fewer than 50 cases of IDDDFP have been reported, highlighting the scarcity of essential research data regarding the correlation between disease phenotypes and genotypes [3,[5][6][7][8][9][10][11][12][13]. In this study, we present a case involving a Chinese family exhibiting typical IDDDFP features, with the proband also presenting with infantile epilepsy and developmental delay.…”
mentioning
confidence: 97%
“…Common clinical features of IDDDFP include intellectual disability (ID), global developmental delay, hypotonia, facial dysmorphisms, ptosis, and/or blepharophimosis. Less frequently reported clinical features include hand and foot anomalies, brain anomalies, microcephaly, behavioral anomalies, growth retardation, and seizures [1][2][3][4][5][6][7][8][9]. Maternal mosaicism has been previously reported in Yan et al [2].…”
Section: Discussionmentioning
confidence: 93%
“…Those without reported phenotypic information were not included in our analysis [ 24 26 ]. Three patients from Mattioli et al [ 1 ] and one patient from Abarca-Barriga et al [ 5 ] were also excluded as they have larger multigene deletions.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the cardiac anomaly has not been widely reported (6/31). Small patent ductus arteriosus, atrial septal defect (Abarca‐Barriga et al, 2022; Yan et al, 2017), and sinus AV nodal pauses and blocks (Yan et al, 2020) were reported up to this point. Additionally, our patients demonstrated patent ductus arteriosus and large ventricular septal defect.…”
Section: Discussionmentioning
confidence: 95%